Hyperthermia and radiotherapy with or without chemotherapy in locally advanced cervical cancer: a systematic review with conventional and network meta-analyses. (2nd October 2016) - Datta, Niloy R.; Rogers, Susanne; Klingbiel, Dirk; Gómez, Silvia; Puric, Emsad; Bodis, Stephan
Abstract: Purpose: A systematic review with conventional and network meta-analyses (NMA) was conducted to examine the outcomes of loco-regional hyperthermia (HT) with radiotherapy (RT) and/or chemotherapy (CT) in locally advanced cervix cancer, IIB–IVA (LACC). Methods and materials: A total of 217 abstracts were screened from five databases and reported as per PRISMA guidelines. Only randomised trials with HT and RT ± CT were considered. The outcomes evaluated were complete response (CR), long-term loco-regional control (LRC), patients alive, acute and late grade III/IV toxicities. Results: Eight articles were finally retained. Six randomised trials with HTRT ( n  = 215) vs. RT ( n  = 212) were subjected to meta-analysis. The risk difference for achieving CR and LRC was greater by 22% ( p  < .001) and 23% ( p  < .001), respectively, with HTRT compared to RT. A non-significant survival advantage of 8.4% with HTRT was noted with no differences in acute or late toxicities. The only HTCTRT vs. RT trial documented a CR of 83.3% vs. 46.7% (risk difference: 36.7%, p  = .001). No other end points were reported. Bayesian NMA, incorporating 13 studies ( n  = 1000 patients) for CR and 12 studies for patients alive ( n  = 807 patients), comparing HTCTRT, HTRT, CTRT and RT alone, was conducted. The pairwise comparison of various groups showed that HTRTCT was the best option for both CR and patient survival. This was also evident on ranking treatment modalities based on the "surface under cumulative ranking" values. Conclusions: In LACC, HTRT demonstrates a therapeutic advantage over RT without significant acute or late morbidities. On NMA, HTCTRT appears promising, but needs further confirmation through prospective randomised trials.